Existentialismus in Österreich: Kultureller Transfer und literarische Resonanz - Werner, Juliane (2021)
The book centers on the Austrian reception of French existentialism, a philosophical-literary movement that had an international impact after the Second World War. It examines how the writing, thinking, and lifestyle of the Parisian circle around Jean-Paul Sartre spread in Austria, be it as a subcultural fashion among young people and artists, as an inspiration for writers and intellectuals, or as a provocation in the eyes of various critics. The material reviewed includes coverage of existentialism in newspapers and magazines, theater performances, and academic research and teaching.